Septic Arthritis in Immunosuppressed Patients: Do Laboratory Values Help?. (March 2020) - Bell, Jared; Rasmussen, Luke; Kumar, Arun; Heckman, Michael G.; Lesser, Elizabeth R.; Whalen, Joseph; Shi, Glenn G.; Wilke, Benjamin K.
Abstract : Introduction: Previous studies have recommended synovial fluid cell count thresholds of 50, 000 cells/mm −3 to diagnose septic arthritis; however, data to support this are limited. It is also unknown if this value is valid in immunosuppressed patients. Methods: We retrospectively reviewed 33 immunosuppressed patients treated at our institution from 2008 to 2018. We compared culture-positive patients with culture-negative patients. Results: We found no statistically significant differences in synovial fluid cell count, percent synovial fluid neutrophils, erythrocyte sedimentation rate, or C-reactive protein between the groups (all P = 0.081). The median synovial fluid cell count in the culture-positive cohort was 29, 000 cells/mm −3, with only 31.2% having >50, 000 cells/mm −3 . Conclusion: Traditional synovial fluid cell thresholds are not a reliable method of diagnosing septic arthritis in immunosuppressed patients.